Towards the theoretical/experimental description of the evolution of material properties at frictional interfaces in metal forming processes. (July 2022) - Alexandrov, Sergei; Jeng, Yeau-Ren; Kuo, Chih-Yu; Chen, Cheng-Yu
Abstract: Frictional interfaces of fabrication processes induce a drastic change in material properties within a thin layer where constitutive equations should be different from those in bulk. This paper focuses on determining two relationships for Aluminum 6061 without a conventional formulation of the friction law. One of them connects the layer thickness and the integrated strain rate intensity factor, and the other is the hardness at the friction surface and the integrated strain rate intensity factor. Plane strain extrusion is used as testing to provide experimental data. This general methodology applies to any ductile materials and other processes can provide experimental data.